China's Nonfinancial Corporate Debt Dynamics. (18th January 2016) - Yu, Yongding; Lu, Ting
Abstract: Since the global financial crisis broke out in 2008, China's nonfinancial corporate debt has been rising steadily and rapidly, posing serious threat to China's financial stability. China's rising corporate debt is mainly attributable to three factors: worsening capital efficiency, worsening corporate profitability and high funding costs. Based on a dynamic recursive model developed in the paper, we simulate the trajectories of China's corporate debt‐to‐GDP ratio, and find that if China fails to reverse the current trends in capital efficiency, corporate profitability and financing costs, China's nonfinancial corporate debt‐to‐GDP ratio will continue to rise without converging to a limit. Against most economists' intuition, given the current trends of changes in parameters, higher economic growth will not help China to escape the corporate debt trap. On the contrary, it will make China's corporate debt problem even worse. To avert a corporate debt crisis, China needs to speed up the structural reform and change the growth paradigm so as to enhance capital efficiency and firms' profitability, while reducing firms' financing costs.